(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
Black scurf disease caused by Rhizoctonia solani is a main yield limiting factor for potato tuber production as it leads to plant death. The present study aimed to isolate naturally occurring antagonistic bacteria that could control R. solani. Bacillus sp. was selected among of 84 isolates secured from rhizosphere of healthy potato plant based on its ability to suppress the growth of the pathogen R. solani. Phylogenetic analysis of this strain based on 16S rRNA gene sequences showed highest similarity (99%) with Bacillus sp.; it was deposited in the GenBank under the accession number of MK030136. The strain culture filtrate containing protease, diffusible antibiotic, hydrogen cyanide and siderophore was capable of inhibiting growth of the pathogen up to 15 days compared to 7 and 10 days for other Bacillus isolates. It also produces indole acetic acid which promoted plant growth. Morphological and structural changes that took place as a result of Bacillus sp. and R. solani interaction were evaluated using light, scanning and transmission electron microscopies. The results showed that Bacillus sp. caused loss of structural integrity, abnormal coiling, shriveling and lysis of the R. solani hyphae, in addition to complete cytoplasm and internal organelles depletion. The Bacillus sp. under study was immobilized on nanoclay to form a bionanocomposite, which was stable and exhibited the biocontrol efficiency along 8 months storage. Both in vitro and greenhouse experiments showed high inhibition of R. solani radial growth. Results indicate that the prepared bionanocomposite is a promising alternative to the commercial products.